Cybervetting is the latest symptom of a deeper problem - Brink, Kyle E. (Industrial and organizational psychology, 2022)
Broad federal laws prohibit discrimination related to several protected classes including race, color, national origin, sex, and religion (under Title VII of the Civil Rights Act of 1964); age (under the Age Discrimination in Employment Act of 1967); and disability (under the Americans with Disabilities Act of 1990). [...]if cybervetting is used to make selection decisions (such as who does or does not advance to the next step in the selection process, who is or is not extended a job offer, etc.), then it is subject to these employment discrimination laws. (2022) provide a compelling argument for why adverse impact would be expected with the typical unreliable, casual, unsystematic, “fuzzy” cybervetting selection process. [...]it would be prudent for organizations to assume that, if the cybervetting selection procedure is challenged, plaintiffs would prevail in showing adverse impact. [...]in anticipation of the potential need for a Phase 2 defense, organizations should ensure that the use of cybervetting is valid and job related. Plaintiffs could also prevail by identifying more structured, standardized, and reliable methods of administering the selection procedure. [...]if organizations insist on using cybervetting as part of the selection process, it behooves them to make the process as fair and reliable as possible.